Traces of the Dynamics of Hadith Narration in Madrasah Kufah: Inheritance of Knowledge and Tradition - Muhammad Sulaiman; Engkos Kosasih; Isra Mardi; Omid Asemani; Kabuye UthmanSulaiman (Cakrawala: Journal of Religious Studies and Global Society, 2025)
Kufa is one of the strategic cities in the history of Islamic civilization that has made a great contribution to the development of hadith science. Founded during the time of Caliph Umar bin al-Khattab, Kufa developed into an intellectual center inhabited by companions and tabi'in, as well as an important arena for the transmission and study of hadith. This city is not only known as the location of hadith narration, but also as a place for the growth of various schools of fiqh and theological thought that influenced the formation of Islamic scientific methodology. This research aims to examine the traces and dynamics of hadith narration in the Kufa madrasah, by tracing the contributions of scholars, the development of scientific institutions, and the influence of socio-political situations on the transmission of hadith. This study uses a qualitative approach with historical methods and literature analysis, focusing on classical sources and contemporary studies of the hadith and intellectual history of Kufa. The results of the study show that hadith madrassas in Kufah developed in a dynamic socio-political context and full of sectarian debates. Kufa scholars developed a rational and critical approach to the narration of hadith, which had a significant impact on the development of hadith science and fiqh thought. Political dynamics and the emergence of various schools of thought such as Shi'ah, Khawarij, and Ahlus Sunnah also shaped the plural and analytical scientific character of Kufa. Thus, the hadith madrassas in Kufa not only inherited a strong tradition of hadith transmission, but also made an influential methodological contribution to the history of Islamic science. This study emphasizes the importance of Kufa's position as the epicenter of hadith science that continues to have an impact on the development of Islamic studies to the present day.